MBL2 polymorphisms in women with atypical squamous cells of undetermined significance. - Zupin, Luisa; Polesello, Vania; Casalicchio, Giorgia; Freato, Nadia; Maestri, Iva; Comar, Manola; Crovella, Sergio; Segat, Ludovica (J Med Virol, 2015)
Infection with high risk Human papillomavirus (HPV) is the main known cause of cervical cancer. HPV induces different grades of lesions: among them, Atypical squamous cells of undetermined significance are abnormal lesions that could evolve in pre-cancer lesions or spontaneously regress. The mannose binding lectin (MBL) is an innate immunity serum protein also found in cervico-vaginal mucosa, whose expression is known to be affected by polymorphisms in exon 1 and promoter of the MBL2 gene. In the present study the possible association between MBL2 functional polymorphisms and susceptibility to develop atypical squamous cells of undetermined significance was investigated in a group of women from North-East of Italy, stratified for HPV infection status. The MBL2 D and O alleles and the deficient producer combined genotypes, responsible for low MBL production, were more represented among atypical squamous cells of undetermined significance positive women than healthy controls and the results were confirmed when only HPV negative samples were considered. These results suggest a possible involvement of MBL2 functional polymorphisms in atypical squamous cells of undetermined significance susceptibility.
Keywords: Adolescent; Adult; Atypical Squamous Cells of the Cervix; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Italy; Mannose-Binding Lectin; Polymorphism, Single Nucleotide; Young Adult